Inequality generating processes and measurement of the Matthew effect - Miia Bask; Mikael Bask (Uppsala University, Department of Economics, 2010)
The first aim of this paper is to clarify the differences and rela-tionships between cumulative advantage/disadvantage and the Matthew ef-fect. Its second aim, which is also its main contribution, is not only to present a new measure of the Matthew effect, but also to show how to esti-mate this effect from data and how to make statistical inference. We argue that one should utilize the positivity of the natural logarithm of the largest generalized eigenvalue for a non-linear dynamic process as evidence when claiming that the Matthew effect is present in the dynamic process that gene-rates individuals'; socio-economic life-courses. Thus, our measure of the Matthew effect focuses on the dynamic process that generates socio-economic inequality and not on the outcome of this process.
urn:nbn:se:uu:diva-133120
Keywords: C02; D63; I31; Z13; 330; cumulative advantage; cumulative disadvantage; dynamic process; inequality; inter-individual change; intra-individual change; life-course; Matthew effect and socio-economic status; Soziale Ungleichheit; Social Capital; Lebensverlauf; Messung; Theorie